Animal or plant: which is the better fog water collector? - Thomas Nørgaard; Martin Ebner; Marie Dacke (PLoS ONE, 2012)
Occasional fog is a critical water source utilised by plants and animals in the Namib Desert. Fog basking beetles (Onymacris unguicularis, Tenebrionidae) and Namib dune bushman grass (Stipagrostris sabulicola, Poaceae) collect water directly from the fog. While the beetles position themselves optimally for fog water collection on dune ridges, the grass occurs predominantly at the dune base where less fog water is available. Differences in the fog-water collecting abilities in animals and plants have never been addressed. Here we place beetles and grass side-by-side in a fog chamber and measure the amount of water they collect over time. Based on the accumulated amount of water over a two hour period, grass is the better fog collector. However, in contrast to the episodic cascading water run-off from the grass, the beetles obtain water in a steady flow from their elytra. This steady trickle from the beetles' elytra to their mouth could ensure that even short periods of fog basking--while exposed to predators--will yield water. Up to now there is no indication of specialised surface properties on the grass leafs, but the steady run-off from the beetles could point to specific property adaptations of their elytra surface.